¿Qué es reforma del Estado? - Lynch, Nicolas (2007)
This papel' examines the COIl(;q)fS ofState. reform of the Suue and the processes ofpolitical democratization in Latiu Americe and Pe/'1I (J{ (he beginnins; of'the :} / si cent IIIT, 11 explores public opinion about the Peru+ian SWl(!, (he contradictions between State and market econotuy aud finallv propases threc processes: nationalizauon. dcmocratization (//1(1dcsprivtuizucion [FrITePeruvian Statc is to achievc htgi/il//üc\' as tlu: politicul authoritv ofthe citizens